Fluxos globais e intra-urbanos : subsídios para seu planejamento em Vitória - Assis, Leandro Camatta de (2009)
One is about a study of the interactions and conflicts between the distinct scales of the flows of the global production and urban mobility on the territory of the city, particularly of Vitória, Espírito Santo. From this analysis of the consequences of th